1998
DOI: 10.1007/s004180050263
|View full text |Cite
|
Sign up to set email alerts
|

The murine calcium-sensitive chloride channel (mCaCC) is widely expressed in secretory epithelia and in other select tissues

Abstract: The tissue and cellular expression pattern of a recently cloned murine calcium-sensitive chloride channel (mCaCC) was determined. In situ hybridization was performed on formalin-fixed, paraffin-embedded murine tissues using digoxigenin-labeled, single-stranded RNA probes. The data were substantiated with northern blot and reverse transcriptase-polymerase chain reaction analyses. All three assays consistently indicated strong expression in tissues with secretory or ion regulatory functions, such as mammary glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
74
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 35 publications
11
74
0
Order By: Relevance
“…54 Stimulation of these receptors may promote anion transport both in biliary 18,21,22 and pancreatic 55 duct epithelial cells, at least transiently. 19,20 Interestingly, ATP stimulated HCO 3 Ϫ secretion only in the presence of elevated intracellular cAMP as previously shown. 18 In both control and CF cholangiocytes continuous presence of ATP (100 mol/L) alone had no stimulatory effect on the basal rate of HCO 3 Ϫ secretion (Figs.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…54 Stimulation of these receptors may promote anion transport both in biliary 18,21,22 and pancreatic 55 duct epithelial cells, at least transiently. 19,20 Interestingly, ATP stimulated HCO 3 Ϫ secretion only in the presence of elevated intracellular cAMP as previously shown. 18 In both control and CF cholangiocytes continuous presence of ATP (100 mol/L) alone had no stimulatory effect on the basal rate of HCO 3 Ϫ secretion (Figs.…”
Section: Discussionsupporting
confidence: 67%
“…In addition to cAMP-stimulated Cl Ϫ channels, Ca 2ϩ -activated Cl Ϫ conductances have also been described in both murine 19,20 and human biliary epithelial cells, 21,22 but their relationship to HCO 3 Ϫ secretion and their function in CFTR-deficient cells are unknown. We studied these relationships in both control and CFTR-deficient human bile duct cells.…”
mentioning
confidence: 99%
“…hCLCA2 belongs to a recently discovered family of proteins, currently comprising about a dozen members, that are widely expressed in mammals but apparently not beyond (19 -28). Various family members are found in epithelia, endothelia, and smooth muscle of multiple organs (21,24,25,27,28). CLCAs do not resemble any other known Cl Ϫ channel (i.e.…”
mentioning
confidence: 98%
“…The family is deeply divergent, some members sharing as little as 36% identity, yet all share certain signatory features. The prototypical CLCA family member is a type I transmembrane protein about 900 amino acids in length with a proteolytic cleavage near amino acid 680 that results in products of 90 kDa and 30 -40 kDa that are found in close association on the exterior surface of the plasma membrane (19,24,26,28). Another common feature is a symmetrical multiple-cysteine motif, CX 12 CX 4 CX 4 CX 12 C, in the amino-terminal tail.…”
mentioning
confidence: 99%
“…I n a s t u d y o f p o t a s s i u m c h a n n e l s i n spermatocytes, in situ hybridization for the mRNA of slo3, a pH-sensitive potassium channel, showed that its expression was largely restricted to spermatocytes [19]. Other channels were also localized in sperm [20][21][22][23]. It is possible that SKD3 has effects on the opening of several potassium channels or the transcription of their mRNAs in Leydig and/or Sertoli cells.…”
Section: Discussionmentioning
confidence: 99%